Factors Affecting Financial Performance in Non-Cyclicals Consumer Sector Companies - Wicaksono, Devita Aprilia; Hariyanto, Eko; Santoso, Suryo Budi; Dirgantari, Novi (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study aims to understand the effects of capital structure, liquidity, corporate size and asset management on financial performance. The data used in this study are secondary data in theform of financial statements. The data analysis method used in this study is multiple linear regression analysis. The sample in this study is Consumer Non-Cyclicals sector companies listed on the Indonesia Stock Exchange (BEI) for the 2019-2021 period. The sampling technique used was purposive sampling and was obtained with 69 company data. Based on research results it can be concluded that capital structure negatively affects financial performance, liquidity has no effect on financial performance, corporate size has no effect on financial performance and asset management has a positive effect on financial performance.